Vaginal fibroleiomyoma in a cow: a case report - Timurkaan, N.; Aydin, M.; Yilmaz, F.; Cevik, A. (Czech Academy Agricultural Sciences, 2009)
This paper describes a case of fibroleiomyoma seen in the vagina of a cow, diagnosed on the basis of macroscopic, microscopic and immunohistochemical findings. A five year-old female, Simmental and Brown Swiss crossbreed cow presented with six neoplastic masses located on the vaginal wall. The masses were surgically removed through the vaginal route and were firm and well demarcated. Microscopic examination showed that the non-encapsulated neoplastic nodules consisted of the admixture of smooth muscle and connective tissue. Immunohistochemical examination revealed strong focal positive reactions for smooth muscle actin and vimentin, but no positive reaction for CD 68. The tumour reported here was considered benign because of the lack of clear pleomorphism, invasivness, multinuclear giant cells and atypia, and low mitotic activity.
Keywords: vagina; fibroleiomyoma; pathology; cow